BRCA1/2 genetic testing uptake and psychosocial outcomes in men - Graves, Kristi D. (2011)
Few studies have quantitatively evaluated the uptake and outcomes of BRCA1/2 genetic counseling and testing in men. We conducted a prospective longitudinal study to describe and compare uptake of and psychosocial outcomes following BRCA1/2 testing in a sample of men and women at high-risk for carrying a BRCA1/2 mutation. Men (n = 98) and women (n = 243) unaffected with cancer completed baseline assessments prior to genetic counseling and testing and then 6- and 12-months post-testing. Most men (n = 94; 95.9%) opted to have genetic testing, of whom 44 received positive BRCA1/2 genetic test results and 50 received true negative results. Among women, 93.4% had genetic testing, of whom 79 received positive results and 148 received negative results. In multivariate models, male BRCA1/2 carriers reported significantly higher genetic testing distress (6-months: Z = 4.48, P < 0.0001; 12-months: Z = 2.78, P < 0.01) than male non-carriers. After controlling for baseline levels of distress, no statistically significant differences emerged between male and female BRCA1/2 carriers in psychological distress at 12-months post-testing, although absolute differences were evident over time. Predictors of distress related to genetic testing among male carriers at 12-months included higher baseline cancer-specific distress (Z = 4.73, P < 0.0001) and being unmarried (Z = 2.18, P < 0.05). Similarly, baseline cancer-specific distress was independently associated with cancer-specific distress at 6- (Z = 3.66, P < 0.001) and 12-months (Z = 4.44, P < 0.0001) post-testing among male carriers. Clinically, our results suggest that pre-test assessment of distress and creation of educational materials specifically tailored to the needs and concerns of male carriers may be appropriate in this important but understudied high-risk group.